Jawabanmu

2014-06-22T17:30:29+07:00
2x² - (a+1)x + (a+3) = 0
x1 - x2 = √(b²-4ac)
                   a
     1    = √{(-(a+1))² - 4(2)(a+3)}
                             2
     4    = a² + 2a + 1 - 8a - 24
a² - 6a - 27 = 0
(a - 9)(a + 3) = 0
a = 9 atau a = -3
(x1-x2)² = x1² + x2² - 2x1x2
   1²      = x1² + x2² - 2x1x2
x1² + x2² = 2x1x2 + 1
              = 2(a+3) + 1
                       2
Untuk a = 9 maka x1² + x2² = 2(9+3) + 1 = 25/2
                                                     2
Untuk a = - 3 maka x1² + x2² = 2(-3+3) + 1  = 1/2
                                                       2